Design of Early Childhood Learning Media on Plant and Animal Life Using Digital Puppetry - I Nyoman Agus Suarya Putra; I Nyoman Yoga Trisemarawima; Ni Wayan Wardani; Wayan Angga Kesuma Muliawan (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2026)
This animal puppetry learning video serves as an interesting alternative to convey educational material to children. Animal puppetry learning videos can stimulate children's imagination and creativity. The animal characters that exist in the puppetry world encourage children to think more broadly and see the world from a new perspective. In this instructional video, the author employed research methods such as observation and interviews, where the author directly visited Dharma Pertiwi Kindergarten to conduct an interview with the headmaster. The interview method involved asking several questions regarding the subject matter and the process of teaching and learning for children at Dharma Pertiwi Kindergarten. Additionally, observations were made by examining literature, materials, curriculum, and how teachers teach children about nature. The process of creating this instructional video involved utilizing puppetry and digital media, skillfully packaged using the Adobe Premiere Pro 2020 application, along with filming using a Lumix G7 mirrorless camera. Consequently, this instructional video was produced, and the results were further enhanced by a questionnaire, which evaluated the effectiveness of the instructional video on the children of Dharma Pertiwi Kindergarten, demonstrating positive outcomes for the instructional media.